Linkage drag constrains the roots of modern wheat. (18th February 2017) - Voss‐Fels, Kai P.; Qian, Lunwen; Parra‐Londono, Sebastian; Uptmoor, Ralf; Frisch, Matthias; Keeble‐Gagnère, Gabriel; Appels, Rudi; Snowdon, Rod J.
Abstract: Roots, the hidden half of crop plants, are essential for resource acquisition. However, knowledge about the genetic control of below‐ground plant development in wheat, one of the most important small‐grain crops in the world, is very limited. The molecular interactions connecting root and shoot development and growth, and thus modulating the plant's demand for water and nutrients along with its ability to access them, are largely unexplored. Here, we demonstrate that linkage drag in European bread wheat, driven by strong selection for a haplotype variant controlling heading date, has eliminated a specific combination of two flanking, highly conserved haplotype variants whose interaction confers increased root biomass. Reversing this inadvertent consequence of selection could recover root diversity that may prove essential for future food production in fluctuating environments. Highly conserved synteny to rice across this chromosome segment suggests that adaptive selection has shaped the diversity landscape of this locus across different, globally important cereal crops. By mining wheat gene expression data, we identified root‐expressed genes within the region of interest that could help breeders to select positive variants adapted to specific target soil environments. Abstract : Roots are of immense importance for environmental adaptation but are largely unexplored in major crops. Via high‐resolution linkage disequilibrium mapping, we discovered strong linkage drag in European wheat between a haplotype variant controlling heading date and two flanking loci carrying alleles that constrain root biomass. Investigation of genes within the region of interest could help breeders to recover root diversity for future food production in fluctuating environments.